2019
DOI: 10.1093/jas/skz258.156
|View full text |Cite
|
Sign up to set email alerts
|

76 Does supplemental protein and rumen-protected methionine improve performance and digestibility during late-gestation in beef cows?

Abstract: Methionine (MET) is likely the first limiting amino acid in low-protein forages fed to beef cattle during late-gestation. Therefore, the objective of this study was to determine if supplemental protein and rumen-protected MET improve cow performance and apparent tract digestibility (TTD) during late-gestation. This study used 147 late-gestation Angus crossbred cows and heifers in a 3x2 factorial arrangement for dietary treatments. The cattle were randomly assigned to one of six diets formulated to 90, 100 or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
(159 reference statements)
1
3
0
Order By: Relevance
“…Methionine hydroxy analog supplementation during late gestation did not affect calf birth weight, which agrees with other studies in beef heifers ( Moriel et al, 2020 ) and cows ( Clements et al, 2017 ; Collins et al, 2019 ; Palmer et al, 2020 ). Periconceptional MHA supplementation did not affect calf birth weight ( Silva et al, 2021 ), but RPMet supplementation for 90 d prior to calving ( Moisá et al, 2019 ) tended to increase calf birth weight in primiparous females.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Methionine hydroxy analog supplementation during late gestation did not affect calf birth weight, which agrees with other studies in beef heifers ( Moriel et al, 2020 ) and cows ( Clements et al, 2017 ; Collins et al, 2019 ; Palmer et al, 2020 ). Periconceptional MHA supplementation did not affect calf birth weight ( Silva et al, 2021 ), but RPMet supplementation for 90 d prior to calving ( Moisá et al, 2019 ) tended to increase calf birth weight in primiparous females.…”
Section: Discussionsupporting
confidence: 91%
“…Glucose concentration was not affected by dietary treatment, agreeing with previous MHA supplementation in B. indicus -influenced beef heifers ( Moriel et al, 2020 ) and early lactating dairy cows ( Michelotti et al, 2021 ). Collins et al (2019) observed greater serum glucose during late gestational RPMet supplementation in beef cows; however, Palmer et al (2020) noted peripartum MHA supplementation resulted in lower glucose in lactation. Socha et al (2008) reported that glucose was not affected by methionine infusions during peak or mid lactation; however, a quadratic increase was observed during early lactation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Maternal AA supply during late gestation affects neonatal calf performance and immune responses ( 12 , 53 , 61 ), which agrees with the results from the current study. Nutrients in the diets of pregnant dairy cows are repartitioned toward colostrum production or fetal growth ( 62 ). Supplying RPM to pre-calving dairy cows affects fetal programming via changes in placental metabolism ( 63 ), and RPL may follow the exact mechanism.…”
Section: Discussionmentioning
confidence: 99%